"W Drodze" - bibliografia zawartości czasopisma = "W Drodze" ["En Route"] - the kontent`s bibliography - Stańczak, Wioletta (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
"W Drodze" was a biweekly political and literary magazine, which was issued in Jerusalem from 1943 until 1946. The title of the magazine defi-nes its leitmotiv, constant abiding "en route" that can be understood symbolically. The history of our country is a continuous journey towards freedom, the road to independence, and the wandering fate of Polish soldiers and civilians.
Keywords: żołnierz; czasopismo; patriotyzm; "W Drodze" - czasopismo; historia; soldier; magazines; patriotism; history